Charlton, Linda. Jane Austen and Reflective Selfhood: Rereading the Self. London: Palgrave Macmillan, 2022. 259 pp. 978-3-031-12159-3 - Simon, Rebeka Petra (FOCUS: Papers in English Literary and Cultural Studies, 2022)
The scholarly discourse surrounding Jane Austen is ever growing. One of its most frequently discussed topics is related to her remarkable ability to portray the complexities of human relationships. In 2020 Tom Keymer published his book Writing, Society, Politics on Austen and addressed the scholarly criticism of her novels, including feminism, narrative techniques, and politics. In the same year, The Cambridge Edition of the Works of Jane Austen was published electronically to reach a wider audience. Linda Charlton’s book Jane Austen and Reflective Selfhood: Rereading the Self is a contribution to this tradition; however, her analysis examines Austen’s works through the lens of eighteenth-century philosophies of selfhood. Charlton argues that Austen’s works interact with fundamental problems of individual identity and moral judgment. She delves into the complexities of Austen’s characters and their journeys of self-discovery to show how Austen provides an insight into the nature of selfhood and personal transformation. Furthermore, Charlton relates the reading practices of characters to their capacity for self-recognition. The book’s eight chapters provide detailed close readings of Austen’s fiction, allowing readers to explore the nuances and intricacies of her characters and their journeys of self- formation.